A clinic-based healthcare transition preparation program for adolescents and young adults with type 1 diabetes: Study protocol for the SHIFT randomized clinical trial - Laura J. Caccavale; Randi Streisand; Jessica Gokee LaRose; Edmond P. Wickham, III; Marisa E. Hilliard; Laura M. Thornton; Melanie K. Bean (Contemporary Clinical Trials Communications, 2025)
Background: A striking 83 % of adolescents and young adults (AYA) with type 1 diabetes (T1D) have glycemic outcomes outside the target range, placing them at risk for acute and chronic complications. Identification of evidence-based strategies to enhance T1D management in AYAs, prior to the transition from pediatric to adult healthcare, is needed to optimize AYA health and adequately prepare them for independence. We present the design of Supporting Health Improvement for Transition in T1D (SHIFT), a randomized clinical trial of a clinic-based transition preparation intervention for AYAs with T1D. Methods: Participants will be 50 AYAs with T1D (age 16–22 years) and their parent/caregiver, and 10 pediatric endocrinology practitioners. All practitioners will receive video education about their role in preparing AYAs for transition and strategies for communication with AYAs. Families will be randomized to either: 1) SHIFT, a 6-month multisystem transition preparation program, or 2) enhanced treatment as usual (TAU+). SHIFT includes evidence-based content across 3 domains: psychoeducation/skill building, behavioral self-management, and practitioner communication. Parents in SHIFT receive psychoeducation and training in developmentally-appropriate parenting strategies to support their AYA in increasing independent self-management and preparing for transition. TAU + includes usual care plus patient education matched to the intervention contact schedule. Assessments of hemoglobin A1c, transition readiness, and diabetes self-management behaviors will occur at 0 (baseline), 6 (post; primary endpoint), and 9 and 12 (follow-ups) months. Conclusion: Findings regarding intervention preliminary efficacy will be the foundation of future fully-powered trials on healthcare transition for AYAs with T1D. Trial registration: NCT05639088.